PENALIZATION THE AUTHORIZER BASED ON THE PARTICIPATION IN THE GRANTING OF POWER OF ATTORNEY - PADMA D. LIMAN (Awang Long Law Review, 2021)
The granting of power of attorney is a common thing in the world of commerce and in daily activities. When a person is unable to directly carry out a legal relationship or a legal action, this act can be authorized to another person, as long as the person receiving the power of attorney is a capable person. The consequences arising from the granting of this power of attorney are borne by the power of attorney as long as the recipient of the power of attorney carries out the same actions as those authorized. Meanwhile, if the recipient of the power of attorney carries out an act that exceeds or is not in accordance with the authorized person, the consequences are borne by the recipient of the power of attorney and frees the power of attorney from the responsibility for the actions of the recipient of the power of attorney. This is clearly regulated in Chapter XVI of Burgerlijk Wetboek (BW) concerning the Granting of Power. However, in its implementation, especially in criminal acts of corruption, it is often the case that the power of attorney is also charged with responsibility for the criminal act of the Authorized Person who exceeds the limit of granting the power of attorney or deviates from the grant of the power of attorney given. The basis for punishing the Authorizer is to use the terms of participation (deelneming) or participation as regulated in the Criminal Code. This paper aims to provide a proper understanding of the position of the Authorizer so that there is no criminalization of the Authorizer for the actions of the Power of Attorney that exceed the powers granted, which lead to criminal acts. The writing method used is the normative juridical approach, which clarifies the understanding of the granting of power of attorney, the recipient of the power of attorney and the author of the power of attorney based on the provisions in the BW so that there are no errors in determining the perpetrators of criminal acts based on the Criminal Code. In this paper, firstly, the granting of power of attorney will be followed by participation and finally, criminal liability will be discussed, so that it can be understood that it is appropriate for the attorney to be subject to a crime based on the participation provisions stipulated in Article 55 paragraph (1) number 1e of the Criminal Code, as a result of criminal acts committed by the recipient of the power of attorney.